Why do employers bargain at particular levels? : a longitudinal case study of Western Cape Clothing Employers' perceptions and behaviour with regard to levels of collective bargaining, 1991-1995 - Godfrey, Shane (Department of Sociology, 2015)
Bibliography: leaves 181-188.